Electrical injury in pediatric patients - A case series - K Mathangi Ramakrishnan; Bala Ramachandran; K G Ravikumar; K Ravikumar; Sulochana Putli; V Jayaraman; T Mathivanan; R Ravi; S Gnanamani; Mary Babu (Wolters Kluwer Medknow Publications, 2020)
Electrical injuries in children are gruesome injuries that result in disabilities and death in developing countries. In this article we present a series of 6 children who were treated for electrical burns. Reconstructive surgery followed by prolonged rehabilitation is required.